Ribbon α-Conotoxin KTM Exhibits Potent Inhibition of Nicotinic Acetylcholine Receptors - Marquart, Leanna A. (Mar Drugs, 2019)
KTM is a 16 amino acid peptide with the sequence WCCSYPGCYWSSSKWC. Here, we present the nuclear magnetic resonance (NMR) structure and bioactivity of this rationally designed α-conotoxin (α-CTx) that demonstrates potent inhibition of rat α3β2-nicotinic acetylcholine receptors (rα3β2-nAChRs). Two bioassays were used to test the efficacy of KTM. First, a qualitative PC12 cell-based assay confirmed that KTM acts as a nAChR antagonist. Second, bioactivity evaluation by two-electrode voltage clamp electrophysiology was used to measure the inhibition of rα3β2-nAChRs by KTM (IC(50) = 0.19 ± 0.02 nM), and inhibition of the same nAChR isoform by α-CTx MII (IC(50) = 0.35 ± 0.8 nM). The three-dimensional structure of KTM was determined by NMR spectroscopy, and the final set of 20 structures derived from 32 distance restraints, four dihedral angle constraints, and two disulfide bond constraints overlapped with a mean global backbone root-mean-square deviation (RMSD) of 1.7 ± 0.5 Å. The structure of KTM did not adopt the disulfide fold of α-CTx MII for which it was designed, but instead adopted a flexible ribbon backbone and disulfide connectivity of C2–C16 and C3–C8 with an estimated 12.5% α-helical content. In contrast, α-CTx MII, which has a native fold of C2–C8 and C3–C16, has an estimated 38.1% α-helical secondary structure. KTM is the first reported instance of a Framework I (CC-C-C) α-CTx with ribbon connectivity to display sub-nanomolar inhibitory potency of rα3β2-nAChR subtypes.